Exploring Consumer Intentions towards Second-Hand Clothing among Generation Z in Malaysia - Wan Nur Fazni Wan Mohamad Nazarie; Aina Hafiza Roslan; Muhamad Firdaus Ab Rahman; Mohamad Hanif Abu Hassan; Wahidah Shari (Akademia Baru Publishing, 2025)
Indexed